The Trinity with Saints formerly Attributed to Jacopo Palma the Younger - Dóra Fekete; Judit Fiam; Edit Miko; Rebeka Tisla (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
In the 2015/16 academic year the conservation of a 16th century canvas painting formerly attributed to Jacopo Palma took place at the Conservation Department of the Hungarian University of Fine Arts. The darkened varnish layers and the severe deterioration caused by water damage made the conservation of the painting necessary. A series of technical examinations were carried out. Photographic examination (IR-reflectography, X-radiography, UV-fluorescence, raking light images) and examination of the cross sections of the samples taken from the painted surface (normal, fluorescent and polarized light microscopy and microchemical tests) made it possible to describe the materials and the painting process.